1988
DOI: 10.1002/ijc.2910420409
|View full text |Cite
|
Sign up to set email alerts
|

Triggering of neoplastic B cells via surface IgM and the cell surface antigens CD20 and CDw40. Responses differ from normal blood B cells and are restricted to certain morphologic subsets

Abstract: By raising monoclonal antibodies (MAbs) against B cells, a number of cell surface molecules have recently been identified which after binding by their specific antibody can trigger B cells, either alone or in co-operation with antibodies to surface immunoglobulin (sIg). The anti-CD20 (Bp35) MAb IF5 can deliver a strong activation signal to resting normal B cells, and the anti-CDw40 (Bp50) MAb G28-5 can promote activated G1 B cells to enter S phase. These antibodies were tested for their functional effects in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The filamentous phage gene3 fragment, which is fused to the single‐chain antibody fragment (scFv) in the library vector in order to enable display on the phage surface, was removed and the expression vector was transformed into SF110 cells 20 . As positive control we used variable domains from G28‐5, 21 cloned into a scFv expression vector (pFab5c) and produced in SF110. Cultures were grown in TB‐medium at 37° to OD 600 =0·5 and then induced with 0·1 m m isopropyl‐thio‐β‐D‐galactoside.…”
Section: Methodsmentioning
confidence: 99%
“…The filamentous phage gene3 fragment, which is fused to the single‐chain antibody fragment (scFv) in the library vector in order to enable display on the phage surface, was removed and the expression vector was transformed into SF110 cells 20 . As positive control we used variable domains from G28‐5, 21 cloned into a scFv expression vector (pFab5c) and produced in SF110. Cultures were grown in TB‐medium at 37° to OD 600 =0·5 and then induced with 0·1 m m isopropyl‐thio‐β‐D‐galactoside.…”
Section: Methodsmentioning
confidence: 99%
“…As a second mechanism of restricting immune responses, the TNFRSF member, HVEM activates an IgSF checkpoint receptor. Interestingly, cooperative signaling via TNF receptors were first recognized with the CD40 system, which enhanced the proliferation of antigen-activated B cells, driven by CD40 Ligand expression in helper CD4 + T cells (Beiske et al, 1988). Cosignaling in B cells is not limited to CD40 as critical survival signals for B cells provided by the BAFFR system underscores the essential nature of this receptor superfamily member in lymphocyte cosignaling (Mackay and Schneider, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Based on their cytomorphological and surface antigen (SIg) features, B-CLL cells were originally considered as the malignant counterparts of small resting B-cells (Robert et al, 1986). However, recent functional studies suggested that B-CLL cells are arrested in an 'activated' state (Beiske et al, 1988) that is reflected by the expression of one or more activation-associated antigens such as FMC7, UCHB1, CD25, B5 or B7 (Table III). Furthermore, the morphology of B-PLL cells and B-CLL cells in 'prolymphocytoid transformation' (CLL-Pro) resembles that described for activated normal B-cells (Melo et al, 1986).…”
Section: Resultsmentioning
confidence: 99%